Passive Immunization with Tau Oligomer Monoclonal Antibody Reverses Tauopathy Phenotypes without Affecting Hyperphosphorylated Neurofibrillary Tangles - Castillo-Carranza, Diana L. (J Neurosci, 2014)
Recent findings suggest that tau oligomers, which form before neurofibrillary tangles (NFTs), are the true neurotoxic tau entities in neurodegenerative tauopathies, including Alzheimer's disease (AD). Studies in animal models of tauopathy suggest that tau oligomers play a key role in eliciting behavioral and cognitive impairments. Here, we used a novel tau oligomer-specific monoclonal antibody (TOMA) for passive immunization in mice expressing mutant human tau. A single dose of TOMA administered either intravenously or intracerebroventricularly was sufficient to reverse both locomotor and memory deficits in a mouse model of tauopathy for 60 d, coincident with rapid reduction of tau oligomers but not phosphorylated NFTs or monomeric tau. Our data demonstrate that antibody protection is mediated by extracellular and rapid peripheral clearance. These findings provide the first direct evidence in support of a critical role for tau oligomers in disease progression and validate tau oligomers as a target for the treatment of AD and other neurodegenerative tauopathies.